2022
DOI: 10.1007/978-3-030-94896-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Alignment of Molecules in Helium Nanodroplets

Abstract: Moderately intense, nonresonant laser pulses can be used to accurately control how gas phase molecules are oriented in space. This topic, driven by intense experimental and theoretical efforts, has been ever growing and developed for more than 20 years, and laser-induced alignment methods are used routinely in a number of applications in physics and chemistry. Starting in 2013, we have demonstrated that laser-induced alignment also applies to molecules dissolved in helium nanodroplets. Here we present an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 203 publications
0
7
0
Order By: Relevance
“…Another remarkable achievement is the demonstration of laser-induced 1D 191 and 3D 192 alignment of molecules dissolved in He nanodroplets, in both the adiabatic and non-adiabatic limits, which significantly extends the range of applications of structural and dynamical investigations. 193 This relies on two main properties: on the one hand, the 0.4 K temperature of the He droplets, shared with the embedded molecules, leads to quite high degrees of alignment (0.96); on the other hand, when using sharply truncated laser pulses, the impeding effect of the He environment on molecular rotation increases up to about 10 ps the time-window of field-free strong alignment, occurring right after extinction of the laser field at the peak of the pulse. This powerful technique opens new perspectives for molecular frame experiments, including ultrafast excited state dynamics, on a variety of large molecules and complexes as demonstrated by 3D alignment of e.g.…”
Section: Experimental Methods and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another remarkable achievement is the demonstration of laser-induced 1D 191 and 3D 192 alignment of molecules dissolved in He nanodroplets, in both the adiabatic and non-adiabatic limits, which significantly extends the range of applications of structural and dynamical investigations. 193 This relies on two main properties: on the one hand, the 0.4 K temperature of the He droplets, shared with the embedded molecules, leads to quite high degrees of alignment (0.96); on the other hand, when using sharply truncated laser pulses, the impeding effect of the He environment on molecular rotation increases up to about 10 ps the time-window of field-free strong alignment, occurring right after extinction of the laser field at the peak of the pulse. This powerful technique opens new perspectives for molecular frame experiments, including ultrafast excited state dynamics, on a variety of large molecules and complexes as demonstrated by 3D alignment of e.g.…”
Section: Experimental Methods and Toolsmentioning
confidence: 99%
“…One obvious fostered perspective is the extension of LF or MF angle resolved PES studies to more complex molecules (finite systems), supported by both recent advances in Coulomb explosion imaging, 459 and the fast improvement of alignment/orientation protocols. 193 This direction also implies specialized methods to produce gas phase targets from different species as mentioned earlier, such as fragile molecules, radicals, positive and negative ions, clusters, nanoparticles, high temperature vapors, and further selection of conformers. 104 Further developments exploring the boundary between gas phase and condensed systems are e.g.…”
Section: Perspectivementioning
confidence: 99%
“…32,33 A recently established technique based on coulomb explosion in combination with correlated velocity map ion imaging of the different fragments allows to decipher the configuration of the initial complex. [34][35][36] This technique is an impressive progress in analyzing the internal structure of a cluster. Since the process of coulomb explosion does not involve a selectivity for individual complex configurations the question arises if this technique allows to identify 6 or even 8 isomeric configurations in a single measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The cold and controlled conditions provided by superfluid helium nanodroplets (He N ) enable the preparation of a wide range of otherwise inaccessible systems, as demonstrated by over three decades of frequency-domain spectroscopy 12 and mass spectrometry. 13 Concerning time-domain studies, the opportunities of He N are currently being explored and a number of photoinduced processes could be identified and characterized, including, among others, molecular alignment, 14 coherent nuclear vibration, 15–17 bond formation, 18 solvent dynamics following electronic excitation, 19–22 internal conversion, 23 quantum beats, 24 intermolecular energy transfer, 25 or nanoplasma formation. 26,27 These seminal studies have shown that, for pump–probe photoionization, the electron kinetic energy can be used as an accurate observable for processes inside He N because the helium-influence on free electrons through binary collisions is sufficiently low.…”
Section: Introductionmentioning
confidence: 99%
“…Ions are only available as observables if they gain sufficient kinetic energy to overcome the attractive droplet potential. Ion ejection from He N has only been reported in a few experiments, where the required energy gain results either from Coulomb repulsion between ions (as applied in Coulomb explosion imaging), 14 or from vibrational excitation by infrared light. 31,32…”
Section: Introductionmentioning
confidence: 99%